Journalistic photography and print media: forms of apprehension - Brandão Tavares, Frederico de M. (2008)
This article underlines the importance of photojournalism as a form of visual representation on daily newspapers. More specifically, it considers what role the relationship between photography and journalism has in the processes of meaning production in newspapers of wide circulation. With this purpose in mind, we will explore some of the aspects and characteristics of the photojournalistic language, as well as its insertion in the media and in the social context.